Non-esterified Fatty Acid Induce Dairy Cow Hepatocytes Apoptosis via the Mitochondria-Mediated ROS-JNK/ERK Signaling Pathway - Li, Yu; Ding, Hongyan; Liu, Leihong; Song, Yuxiang; Du, Xiliang; Feng, Shibin; Wang, Xichun; Li, Xiaobing; Wang, Zhe; Li, Xinwei; Li, Jinchun; Wu, Jinjie; et al. (Frontiers in Cell and Developmental Biology, 2020)
Elevated plasma nonesterified fatty acid (NEFA) levels and hepatocytes damage are characteristics of ketosis in dairy cows. Oxidative stress is associated with the pathogenesis of NEFA-induced liver damage. However, the exact mechanism by which oxidative stress mediates NEFA-induced hepatocytes apoptosis and liver injury remains poorly understood. The results of the present study demonstrated that NEFA contribute to reactive oxygen species (ROS) generation, resulting in an imbalance between oxidative and antioxidant species, transcriptional activation of p53, transcriptional inhibition of nuclear factor E2-related factor 2 (Nrf2), loss of mitochondria membrane potential (MMP) and release of apoptosis-inducing factor (AIF) and cytochrome c (cyt c) into the cytosol, leading to hepatocytes apoptosis. Besides, NEFA triggered apoptosis in dairy cow hepatocytes via the regulation of c-Jun N-terminal kinase (JNK), extracellular signal-regulated protein kinases 1 and 2 (ERK1/2), Bcl-2-associated X protein (Bax), B-cell lymphoma gene 2 (Bcl-2), caspase 9 and poly (ADP-ribose) polymerase (PARP). Pretreatment with the inhibitor SP600125 or PD98059 or the antioxidant N-acetylcysteine (NAC) revealed that NEFA-ROS-JNK/ERK-mediated mitochondrial signaling pathway plays a crucial role in NEFA-induced hepatocytes apoptosis. Moreover, the results suggested that the transcription factors p53 and Nrf2 function downstream of this NEFA-ROS-JNK/ERK pathway and are involved in NEFA-induced hepatocytes apoptosis. In conclusion, these findings indicate that the NEFA-ROS-JNK/ERK-mediated mitochondrial pathway plays an important role in NEFA-induced dairy cow hepatocytes apoptosis and strongly suggests that the inhibitors SP600125 and PD98059 and the antioxidant NAC may be developed as therapeutics to prevent hyperlipidemia-induced apoptotic damage in ketotic dairy cows.